Coping with natural hazards : Indian context - Valdiya, K. S. (Khadg Singh), 1937-; National Academy of Sciences, India; University of Pune. (Hyderabad : Orient Longman, 2004)
Contributed papers presented at a symposium on "Coping with Natural Hazards" held at University of Pune, India, on Oct. 5-6, 2001, in conjunction with the 71st annual session of National Academy of Sciences, India.
"The National Academy of Sciences, Allahabad."
Originally published: 2004.
Includes bibliographical references and index.
Keywords: Natural disasters -- India -- Congresses; Emergency management -- India -- Congresses